Schlaganfall bei akutem Verschluss der A. basilaris: Diagnostik und Therapie - Nagel, Simon (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2017)
Acute occlusion of the basilar artery is a rare and, if left untreated, severe neurovascular condition with a high mortality. The clinical presentation is often atypical and hence diagnosis may be delayed. Because of the devastating natural course, recanalization strategies were often more aggressive than in patients with occlusions in the anterior circulation. To date, there is no evidence-based therapy, and recent larger registry studies and meta-analyses do not show a clear superiority of endovascular approaches over systemic thrombolysis alone. The current review aims to provide an overview of the most critical aspects in clinical and radiological diagnosis and treatment of basilar artery thrombosis.